Surge detecting with a spherical sensor. Issue 2 (21st March 2016) - Tang, Zhijie; Luo, Qian; Leng, Xinnan; Liu, Pinglong; Luo, Jun
Abstract : Purpose: The purpose of this study is to design a spherical sensor which can detect the surge from various directions to lay the foundation of the research of surge. Design/methodology/approach: This paper designed a spherical sensor to detect the impact force generated by the surge. To realize the depth and stability control of the shallow underwater vehicles, it is necessary to do research and analysis on the surge in shallow waters. The spherical sensor with novel structure was skillfully composed of 24 cantilever beam pressure-type strain sensors. It is powerful to detect the surge from various directions simultaneously. Findings: It is proved that the spherical sensor can accurately collect the surge data from multiple directions through experiments, which laid the foundation of the anti-surge study. Research limitations/implications: Surge is not a new topic. But there is no effective tool to detect surge. The research of this paper is an attempt to provide an available tool to analyze surge. The research limitation is that the pool where the spherical sensor is installed is a little small. In the future, a bigger pool can be used. Practical implications: A deep and comprehensive analysis of surge can be conducted according to the surge data detected by the spherical sensor to achieve the essential features of surge. This lays the foundation for the accurate control of Autonomous Underwater Vehicles (AUVs), especially fixed depth and stability control. Social implications: As the control accuracy of AUVs increases, the AUVs can perform much more difficult tasks such as port monitoring, underwater salvaging, underwater pipeline maintenance and so on. These can be applied in commercial applications or in the national defense of many countries. Originality/value: A novel spherical sensor using 24 cantilever beam pressure-type strain sensors to detect the surge was designed. The spherical sensor was installed in the physical surge simulator to collect surge data and conduct an analysis of the collected data.